Cross-cultural Validation of the Nostalgia Scale for Sport Tourism (NSST): A Multilevel Approach. (May 2020) - Cho, Heetae; Joo, Dongoh; Woosnam, Kyle Maurice
This study evaluated the cross-cultural generalizability of the Nostalgia Scale for Sport Tourism (NSST), which was originally developed and examined in the context of football tourists in the United States. Data were collected from baseball tourists in South Korea, and multilevel confirmatory factor analysis and multilevel structural equation modelling were used for data analysis. Results supported the reliability and the validity of the scale both at individual and group levels, revealing an identical five-factor structure across the 29-item scale. Additionally, this study found a significant effect of sport nostalgia on revisit intention both at individual and group levels. The findings indicate that the NSST is applicable in understanding sport tourists' nostalgia across different sport and cultural settings. Implications and suggestions for future nostalgia research are also discussed.